Sexual coercion at first sexual debut and associated factors among young females in rural areas of Boset District, Eastern Ethiopia: A mixed-method study - Sileshi Garoma Abeya (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2021)
Objectives: Assess the prevalence and associated factors of sexual coercion at first sexual debut among young females in rural areas of Boset district, Oromia Region, Ethiopia. Methods: Cross-sectional community-based study was conducted using qualitative and quantitative data collection methods. A sample of 632 young females aged 10-24 years was taken from six rural Kebeles by systematic random sampling for quantitative and data was collected using a pre-tested structured questionnaire. The collected data was analyzed using SPSS version 23. Principally Binary Logistic regression model was fitted. Moreover, eight focus group discussions targeting different groups were held and analyzed thematically. Results: Prevalence of sexual coercion at first sexual debut was 36.5% (95%CI: 34.6%-38.4%) among sexually active respondents. Married young female (AOR,0.71;95%CI: 0.42,0.81), living away from their parents (AOR,5.07;95%CI:1.07,24.01), age group of 15-19 (AOR,0.19; 95%CI:0.06,0.54), alcohol consumption (AOR,2.44;95%CI:1.17, 5.08) and Khat chewing (AOR, 8.30;95%CI:1.89, 36.38) were factors predicting the likelihood of having sexual coercion at sexual debut. Conclusion: Sexual coercion at fist sexual debut is a major public health problem among young females in the study community. The emerging program interventions need to take this problem into consideration.